2013
DOI: 10.1111/aji.12162
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Alternative Complement Pathway Activation in Early Severe Preeclampsia

Abstract: Problem We sought to determine whether alternative complement activation fragment Bb (Bb) levels are elevated in the maternal, fetal, and placental blood in cases of severe preeclampsia (PE) compared with normotensive controls. Method of study This was a cross-sectional study of women admitted at ≥24 weeks gestation with or without severe PE. Maternal plasma was collected at the time of enrollment. Umbilical venous cord and intervillous space blood were collected at delivery. Plasma Bb levels were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 20 publications
3
45
1
1
Order By: Relevance
“…Increased inflammation and activation of the Alternative Complement Pathway in cord blood of babies born to preeclamptic mothers have been observed suggesting that maternal preeclampsia does indeed have consequences for the fetal immune system 22, 23. Bujold et al 20.…”
Section: Discussionmentioning
confidence: 99%
“…Increased inflammation and activation of the Alternative Complement Pathway in cord blood of babies born to preeclamptic mothers have been observed suggesting that maternal preeclampsia does indeed have consequences for the fetal immune system 22, 23. Bujold et al 20.…”
Section: Discussionmentioning
confidence: 99%
“…While not all related studies have been conclusive, both the classical and the alternative CS pathway have been recognized in the pathogenesis of PE. 10,37,38 Bb fragments may represent a sign of the exaggerated alternative CS pathway activation occurring in the early severe PE. 38 Clinical studies reported that CS is activated with increased terminal complex (C5b9) formation in the third trimester of normal human pregnancy, and further in PE.…”
Section: Complement Systemmentioning
confidence: 99%
“…В пользу этого свидетельствует обнаруженное до 20 нед гестации в крови беременных с развившейся впоследствии преэклампсией высокое содержание одного из важных факторов, форми-рующих С3-конвертазу АПК -фрагмента комплемента Bb [14]. Позже был продемонстрирован повышенный уровень Bb в плазме крови пациенток с рано развившейся (до 34 нед беременности) тяжелой преэклампсией и в ве-нозной пуповинной крови детей, рожденных этими мате-рями, по сравнению с таковыми у женщин с неосложнен-ным течением беременности, что подтвердило важную роль системной активации АПК в развитии преэкламп-сии [16]. Кроме того, оказалось, что комплементы актива-ции комплемента, особенно фрагмент С5а, стимулируют продукцию моноцитами растворимых рецепторов к фак-тору роста эндотелия сосудов (VEGF) -sVEGFR-1 или sFlt1, которые блокируют плацентарные ангиогенные факторы VEGF и PlGF.…”
Section: таблица 3 основные лабораторные показатели в острый период unclassified